Long-term seawater temperature records at Livingston and Deception Islands, Antarctica - Olga Luengo-S; Olga Luengo-S; Belén Rosado; Vanessa Jiménez-Morales; Amós de Gil; Jesús Gómez-Enri; Miguel Bruno; Manuel Berrocoso; Manuel Berrocoso (Frontiers in Marine Science)
This study investigates seawater temperature patterns on Livingston and Deception Islands in Antarctica, where LIVMAR and DECMAR oceanographic stations are located, respectively. The research spans the period from 2015 to 2024, focusing on seasonal variations, long-term trends, and differences between the two stations. Seawater temperature data were analysed over a ten-year period, allowing for the examination of seasonal cycles, temperature extremes, and anomalies. Particular attention was paid to identifying influences from local geophysical features such as volcanic activity and glacial melt. Over these ten years, minimum temperatures have decreased, with DECMAR notably failing to record temperatures below the freezing point during the last two winters. The analysis reveals pronounced seasonality in both locations, with higher temperature peaks during the austral summer. DECMAR consistently registers higher maximum temperatures compared to LIVMAR, attributed to the volcanic activity of Deception Island. This volcanic influence introduces thermal anomalies, delays in minimum temperature occurrence, and greater variability in summer signals due to increased subsurface water flow within the volcanic plumbing system. During the austral winters, the stations exhibit distinct patterns. LIVMAR shows earlier and more variable temperature drops, while DECMAR demonstrates shorter but more stable freezing periods. These differences may result from freshwater input from the Johnson Glacier, which modifies local freezing conditions at Livingston Island, combined with the geothermal influence of Deception Island. The study identifies an overall upward trend in seawater and air temperatures, aligning with global and regional climate change patterns. The reduction in the frequency of extreme low temperature events that occurred between 2020 and 2022 during the volcano-tectonic event in the Bransfield Strait due to the eruption of the Orca volcano highlights the environmental changes affecting the South Shetland Islands region. This work underscores the importance of local geophysical processes, such as volcanic activity and glacier melt, in the regional thermal dynamics. While the similarities between LIVMAR and DECMAR reflect overarching climatic drivers, the observed differences illustrate the complexity introduced by local factors.